STUDY THE EFFECT OF OPERATING OF THE NORTH AND SOUTH AL DIWANIYAH POWER PLANTS ON THE CITY OF AL DIWANIYAH - Hussein, Abdulrazzaq Abdzaid; Alnasur, Fawzi Sh.; Almansoori, Ahmed Ch.; AL-Furaiji, Mushtaq A. (Journal of Applied Engineering Science, 2022)
This study was conducted to find out the impact of two diesel plants (southern and northern) of the city of Al Diwaniyah by studying the concentrations of some heavy elements (Cu, Pb, Zn, Mn and Fe) in the soil and plants around the two stations as a result of operating with heavy fuel and the absence of techniques for filtering exhaust waste. The results showed that heavy metals in plants are higher than their concentration in the soil. Moreover, the highest percentage of contamination with heavy elements for each of Fe, Zn, Mn, Cu and Pb in the soil is 293.1, 133.8, 365, 55, 46 and 0.093 mcg/gm, respectively against, 440, 201.8, 446, 130,98 and 35.12 mcg/gm in the plant. These percentages are higher than the recommended values, according to the World Health Organization (WHO). The results also showed that the pollution level from heavy metals in soil and plant samples was higher in the areas south of the two stations. The lowest values were located to the north of stations because the wind blew from north to south, carrying the pollutants most of the year. This has resulted from the incomplete combustion of heavy fuel in the two plants to the populated city center, located to the south of the North Al Diwaniyah station.